2010
DOI: 10.2176/nmc.50.936
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Epidermoid Tumor With Changes in Signal Intensity on Magnetic Resonance Imaging Because of Non-hemorrhagic Pathology -Case Report-

Abstract: A 61-year-old woman presented an intracranial epidermoid tumor manifesting as dizziness and right facial hypesthesia. Magnetic resonance (MR) imaging revealed a well-defined lobulated mass in the right cerebellopontine angle as nearly isointense to the cerebrospinal fluid (CSF) on both T 1 -and T 2 -weighted images but inhomogeneously hyperintense on fluid-attenuated inversion recovery images. MR imaging performed 1 year later revealed that the tumor had significantly enlarged, and now appeared hyperintense to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…7 In contrast, WECs have a relatively high viscosity and protein concentration because inflammation, infection, and keratin desquamation result in degeneration of the cyst wall and increased protein levels. [8][9][10] The present case also suggested histopathological changes before and after the WEC transformation. As mentioned earlier, there are various reports on the pathological findings of WECs; however, the detailed pathological mechanism of the occurrence of WECs has not been fully clarified.…”
Section: Discussionsupporting
confidence: 52%
“…7 In contrast, WECs have a relatively high viscosity and protein concentration because inflammation, infection, and keratin desquamation result in degeneration of the cyst wall and increased protein levels. [8][9][10] The present case also suggested histopathological changes before and after the WEC transformation. As mentioned earlier, there are various reports on the pathological findings of WECs; however, the detailed pathological mechanism of the occurrence of WECs has not been fully clarified.…”
Section: Discussionsupporting
confidence: 52%
“…3,5 Importantly, sudden development of symptoms and exponential growth of EC with a novel finding of contrast enhancement seen on imaging studies may suggest malignant transformation. 2,4,[14][15][16][17] Although extremely rare, malignant transformation into squamous cell carcinoma confers poor prognosis. 16 Careful histological examination of hyperdense EC lesions is essential to differentiate EC from other diseases, and to rule out malignant transformation, which would require adjuvant therapy after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been reported that hypointensity on T2WI of neurenteric cysts is consistent with squamous metaplasia and voluminous keratinous debris. 2 Muto et al 18 discussed about signal intensity changes in MRI of epidermoid cysts, speculating that the amount of protein, free water, and keratin in the cyst correlate with the inflammation, infection, or desquamation of the cyst wall. In these contexts, we consider that the trigger of MRI signal intensity alterations in our cases might be a chronic inflammation due to a mechanical or a chemical stimulation such as cyst rupture or surgical impact.…”
Section: Discussionmentioning
confidence: 99%